Advances in Oral Drug Delivery for Regional Targeting in the Gastrointestinal Tract - Influence of Physiological, Pathophysiological and Pharmaceutical Factors - Hua, Susan (Frontiers in Pharmacology, 2020)
The oral route is by far the most common route of drug administration in the gastrointestinal tract and can be used for both systemic drug delivery and for treating local gastrointestinal diseases. It is the most preferred route by patients, due to its advantages such as ease of use, non-invasiveness and convenience for self-administration. Formulations can also be designed to enhance drug delivery to specific regions in the upper or lower gastrointestinal tract. Despite the clear advantages offered by the oral route, drug delivery can be challenging as the human gastrointestinal tract is complex and displays a number of physiological barriers that affect drug delivery. Among these challenges are poor drug stability, poor drug solubility, and low drug permeability across the mucosal barriers. Attempts to overcome these issues have focused on improved understanding of the physiology of the gastrointestinal tract in both healthy and diseased states. Innovative pharmaceutical approaches have also been explored to improve regional drug targeting in the gastrointestinal tract, including nanoparticulate formulations. This review will discuss the physiological, pathophysiological and pharmaceutical considerations influencing drug delivery for the oral route of administration, as well as the conventional and novel drug delivery approaches. The translational challenges and development aspects of novel formulations will also be addressed.